Noncontact method of thermal linear expansion coefficient determination for various materials in temperature range 500 to 2500°C - Borzukh, A.S.; Popov, V.P.; Savchenko, V.S.; Skibina, L.V.; Chernik, M.M.; Yushchenko, K.A. (Functional Materials, 2004)
A noncontact method has been developed to determine the thermal linear expansion coefficient (TLEC) of carbon-graphite and ceramic materials and heat-resistant alloys in a temperature range of 500 to 2500 °C. The setup and its functional potentialities are shown schematically. The TLEC values measured on primary standard specimens (electrolytic nickel and commercial APB graphite) differ by at most 5 % from literature reference data. Experimental temperature dependences of relative elongation and TLEC for the high-temperature Rene 80 alloy in the 500-1200 °C interval are presented. A hysteresis is revealed in the Al/l(T) dependence, which is connected with the cooling-induced formation and heating-induced dissolution of the ordered /-phase (Ni3AI). Разработан бесконтактный метод определения термического коэффициента линейного расширения (ТКЛР) углеграфитовых, керамических материалов и жаропрочных сплавов в интервале температур 500-2500°C. Приведена схема установки и показаны ее функциональные возможности. Измеренные значения ТКЛР эталонов (электролитического никеля и промышленного графита АРВ) отличаются от справочных литературных данных не более, чем на 5 % . Представлены экспериментальные данные по температурной зависимости относительного удлинения и термического коэффициента линейного расширения жаропрочного никелевого сплава Rene 80 в области температур 5001200°C. На зависимости Al/l(T) выявлен гистерезис, связанный с образованием при охлаждении и растворением при нагреве упорядоченной /-фазы (Ni3AI). Розроблено безконтактний метод визначення тєрмічного коефіцієнта лінійного розширення (ТКЛР) вуглеграфітових, керамічних матеріалів і жаростійких сплавів в інтервалі температур 500-2500°С. Наведено схему установки і показано її функціональні можливості. Виміряні значення ТКЛР еталонів (електролітичного нікелю і промислового графіту АРВ) відрізняються від довідкових літературних даних не більш, чим на 5 %. Наведено експериментальні дані з температурної залежності відносного подовження і термічного коефіцієнта лінійного розширення жаростійкого нікелевого сплаву Rene 80 в області температур 500-1200°С. На залежності Al/l(T) виявлений гістерезис, який зв’язаний з утворенням при охолодженні і розчиненням при нагріванні впорядкованої Y-фази (Ni3AI).